Analisis Dampak Penggunaan Content Management System (CMS) Open Source Terhadap Industri Portal Berita Media Online - Maulana, Yusep (Institut Teknologi Garut, 2024)
Technological developments in the dissemination of information are increasingly rapid along with the increasing public need for fast and relevant access to information. The journalism industry is also following this trend by providing innovative information, especially through online platforms. Online news portals have become an inseparable part of the development of internet technology in the world of journalism, meeting the needs of an increasingly dynamic audience in seeking information. However, along with the emergence of this new media, especially with the use of social media and the development of journalism in website-based online news portals and mobile applications, there is an increasing need for technology to build online news portals. One technology that is widely used today is an Open Source based CMS, because apart from being cheap and easy to use, it is difficult to find a comparable alternative for building a modern online news portal. However, this research shows that the use of Open Source-based CMS, although it has many advantages, also has a number of problems that can have varying impacts on the long-term business of the online media industry. This research methodology uses a qualitative approach with descriptive research type to gain an in-depth understanding of this phenomenon.